RESULTS OF EVALUATION OF CLINICAL AND INSTRUMENTAL FEATURES OF MYOCARDIAL INFARCTION IN PAROXYSMAL ATRIAL FIBRILLATION - Khasanjanova F.O; Nazarova Z.Sh; Isomiddinova Z.S (Scholar Express Journals, 2024)
In this scientific work, the clinical and instrumental features of the course of myocardial infarction in AF paroxysm were evaluated, thanks to the joint use of methods for evaluating troponin I, ECG, coronary angiography (CAG), transthoracic echocardiography. The study included 128 patients hospitalized in emergency departments No. 1 and 2 and cardiac intensive care units of the Samarkand branch of the Republican Scientific Center for Emergency Medical Care. AF paroxysm can develop against the background of a more serious pathology, such as atherosclerotic damage to the coronary arteries or lead to secondary myocardial damage. The study of troponin levels in this group of patients seems justified.
Keywords: myocardial infarction; atrial fibrillation; troponin; coronary angiography